2017
DOI: 10.4314/ijbcs.v11i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Aspects épidémiologiques du diabète de type 1 à la banque d’insuline de Cotonou (Bénin)

Abstract: RESUMELe diabète sucré, bien qu'étant considéré comme une maladie des pays riches, constitue de plus en plus une préoccupation majeure dans les pays en développement et particulièrement en Afrique subsaharienne. L'objectif de cette étude était de déterminer les caractéristiques sociodémographiques, d'évaluer la fréquence du diabète de type 1 (DT1) et de calculer le taux de mortalité chez les diabétiques de type 1 ayant consultés à la Banque d'Insuline de Cotonou de janvier 1996 à décembre 2015. Une recherche b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Our data corroborate with those found in the literature. [13,14] This can be explained by the fact that T1D is an autoimmune disease caused by the breakdown of tolerance, leading to activated CD4, CD8, and CD28 T lymphocytes, which then change their differentiation pathway to an effector phenotype, thus participating in the destruction of pancreatic β-cells. [15,16] It is also important to consider the role of CMV; multivariate analysis showed that the odds ratio was relatively higher, indicating that (T1D+CMV+) subjects have a 3 times higher chance of having elevated plasma concentrations of CD4, CD8, and CD28 T lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Our data corroborate with those found in the literature. [13,14] This can be explained by the fact that T1D is an autoimmune disease caused by the breakdown of tolerance, leading to activated CD4, CD8, and CD28 T lymphocytes, which then change their differentiation pathway to an effector phenotype, thus participating in the destruction of pancreatic β-cells. [15,16] It is also important to consider the role of CMV; multivariate analysis showed that the odds ratio was relatively higher, indicating that (T1D+CMV+) subjects have a 3 times higher chance of having elevated plasma concentrations of CD4, CD8, and CD28 T lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Avec une proportion plus importante de diabète du type 2. Au Benin ils étaient à 98,8% contre 0,9% du diabète de type 1 (Fagbemi et al, 2017 ;Suvi et al, 2017). Le pré-diabète se caractérise par des anomalies de la glycorégulation avec une glycémie à jeun supérieure ou égale à 6,1 mmol/l (110 mg/dl), mais inférieure à 7,0 mmol/l (126 mg/dl) selon l'Organisation Mondiale de la Santé (OMS).…”
Section: Introductionunclassified